A Mechanistic Approach to Plankton Ecology - Kiorboe, Thomas (Book collections on Project MUSE., 2008)
"This book offers a mechanistic approach to the study of ocean ecology by exploring biological interactions in plankton at the individual level. The book focuses on encounter mechanisms, since the pace of life in the ocean intimately relates to the rate at which encounters happen." "Most of the book's chapters consist of a theoretical introduction followed by examples of how the theory might be applied to real-world problems. In the final chapters, mechanistic insights of individual-level processes help to describe broader population dynamics and pelagic food web structure and function."--Jacket